2010
DOI: 10.1097/jsm.0b013e3181e413df
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammatory Parameters After an Ironman Race

Abstract: An Ironman race provokes significant alterations in oxidative stress and inflammatory parameters. Thus, more studies with other markers and different designs are needed to elucidate the cellular alterations induced by an IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
3
37
0
1
Order By: Relevance
“…22 Pinho et al measured an average weight loss of 2 kg after the Ironman course (3.8 km swimming, 180 km cycling, and 42.2 km running). 23 A previous study found an average weight loss of 2.3 and 2.5 kg after the Ironman race. 19 These values were lower than the 4.2 kg weight loss after the O2 course found in our study, presumably because although the Ironman course is longer than the O2 course, athletes perform the Ironman course with lower exercise intensity than the O2 course, in which the goal is to finish the race.…”
Section: Discussionmentioning
confidence: 99%
“…22 Pinho et al measured an average weight loss of 2 kg after the Ironman course (3.8 km swimming, 180 km cycling, and 42.2 km running). 23 A previous study found an average weight loss of 2.3 and 2.5 kg after the Ironman race. 19 These values were lower than the 4.2 kg weight loss after the O2 course found in our study, presumably because although the Ironman course is longer than the O2 course, athletes perform the Ironman course with lower exercise intensity than the O2 course, in which the goal is to finish the race.…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors, associated with or independent from muscle damage, such as nutritional status and use of antioxidants may influence on the interleukins responses [16][17][18][19] . In the present study, these factors were not controlled, which becomes a limitation of it.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a concomitant increase in the production of reactive oxygen species (ROS) and subsequent oxidative damage to cellular structure because of oxidation of membrane lipids, protein carbonylation, carbohydrate oxidation, and damage to nucleic acids 9 . In addition, other phenomena may prompt the production of ROS during long sports competitions, such as migration of polymorphonuclear cells to the injured tissue and ischemic muscle response 5 . According Cruzat et al 10 , individuals who undergo intense and prolonged exercise or exhaustive training, or even those with very high training frequency may exceed the capacity of endogenous antioxidant system and, consequently, cause severe muscle injuries, with subsequent inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In endurance races, the athletes' physical wear causes a significant energy demand and substantial change in the antioxidant defense mechanisms and reduced cellular repair system 5 . As a result, some studies suggest an increase in oxidative damage of biomolecules due to increased ROS generated mainly via the mitochondrial respiratory chain, incomplete reduction of oxygen, as well as decrease in antioxidant defense system 13,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation